Application of thermogravimetric analysis for thermal characterization of walnut oil and biodiesel. (August 2019) - Tutunea, D; Ilie, D; Racila, L; Geonea, I; Otat, O; Matei, L
Abstract: The biodiesel is being promoted worldwide as an important alternative to petrodiesel fuel due mainly to availability, low emissions and simple industrial production from renewable sources. Analysis of thermal properties is important showing the distillation and decomposition of the fuel function of temperature providing the temperature range of the combustion processes. In this paper physical and thermal properties of walnut oil were analyzed using Thermogravimetry (TGA/DTG). According to the thermograms the walnut oil presents the highest thermal stability in comparison with diesel fuel and walnut oil biodiesel.